Iran's Bomb: A Crisis Deferred? - Donovan, Michael (Tufts Archival Research Center, 2005)
Volume 29, Issue 2. Summer Michael Donovan explains how the United States is uniquely qualified to do what the Europeans wish they could do-stop Iran from developing nuclear weapons without resorting to military force.